Nucleotide sequence of a yeast Ty element: evidence for an unusual mechanism of gene expression. - Clare, J (1985)
We have determined the DNA sequence of the transposable element Ty912 of yeast. The 5918-base-pair element encodes two genes, tya912 and tyb912, which specify proteins similar to sequence-specific DNA-binding proteins of Escherichia coli and retroviral reverse transcriptases, respectively. The tyb912 gene is atypical of eukaryotic genes since (i) it begins 1336 nucleotides into the Ty912 mRNA (i.e., downstream of the tya912 gene) and (ii) the first in-frame AUG is 921 nucleotides into the coding frame. Protein blot analysis of Ty-lacZ fusions shows that the tyb912 gene is translated starting at the 5' end of the tya912 gene and that the primary translational product is a tya912::tyb912 fusion protein. We have shown that synthesis of this fusion protein probably does not occur by RNA splicing. The data are consistent with a mechanism of translational frameshifting occurring within the region of overlap between the 3' end of tya912 and the 5' end of tyb912.